HOW TO IMPROVE YOUR READING AND WRITING - Eshmuradova Shahlo; Eldorbek Khamitov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT: This article provides a comprehensive overview of practical methods and strategies to improve reading and writing skills effectively. It explores various reading techniques such as active reading, skimming, and scanning to enhance comprehension and retention of information. Additionally, it highlights the importance of building a strong vocabulary and understanding grammar to improve writing clarity and coherence. The article also stresses the value of consistent practice, including writing regularly and seeking constructive feedback to identify areas for improvement. By addressing common challenges faced by learners, such as difficulty in organizing ideas or understanding complex texts, this article aims to equip readers with the necessary tools to become more confident and proficient readers and writers. Ultimately, it encourages a balanced approach that combines reading widely with deliberate writing practice to foster overall language development.